Sketching user experiences getting the design right and the right design - Buxton, William (Amsterdam ; Boston : Elsevier/Morgan Kaufmann, 2007)
Bill Buxton and I share a common belief that design leadership together with technical leadership drives innovation. Sketching, prototyping, and design are essential parts of the process we use to create new products. Bill Buxton brings design leadership and creativity to Microsoft. Through his thought-provoking personal examples he is inspiring others to better understand the role of design in their own companies--Bill Gates, Chairman, Microsoft"Informed design is essential." While it might seem that Bill Buxton is exaggerating or kidding with this bold assertion, neither is the case. In
pt. I. Design as dreamcatcher -- Design for the wild -- Case study : Apple, design, and business -- The bossy rule -- A snapshot of today -- The role of design -- A sketch of the process -- The cycle of innovation -- The question of "design" -- The anatomy of sketching -- Clarity is not always the path to enlightenment -- The larger family of renderings -- Experience design vs interface design -- Sketching interaction -- Sketches are not prototypes -- Where is the user in all of this? -- You make that sound like a negative thing -- If someone made a sketch in the forest and nobody saw it ... -- The object of sharing -- Annotation : sketching on sketches -- Design thinking and ecology -- The second worst thing that can happen -- A river runs through it -- pt. II. Stories of methods and madness -- From thinking on to acting on -- The wonderful Wizard of Oz -- Chameleon : from wizardry to smoke-and-mirrors -- Le Bricolage : cobbling things together -- It was a dark and stormy night ... -- Visual story telling -- Simple animation -- Shoot the mime -- Sketch-a-move -- Extending interaction : real and illustion -- The bifocal display -- Video envisionment -- Interacting with paper -- Are you talking to me?
Includes bibliographical references (p. 422-435) and index.
Keywords: Industrial design; Design, Industrial; Electronic books